Cuentos clásicos juveniles - Pushkin, Alexander; Wilde, Oscar; Maupassant, Guy de; Dostoievski, Fiódor; Tolstoi, León; Twain, Mark; Eça de Queirós, José María; Zuluaga Osorio, Conrado (Clásicos)
El libro reune cuentos de 7 autores: Alexander Pushkin, Guy de Maupassant, Fiódor Dostoievski, León Tolstoi, Mark Twain, Óscar Wilde, José María Eça de Queirós